PENGARUH DIFERENSIASI PRODUK, DIGITAL MARKETING DANKEBIJAKAN HARGA TERHADAP KEPUTUSAN WISATAWANMENGINAP DI THE COMPASS ROSE UBUD - I Nengah Suweca; Luh Komang Candra Dewi; Sourtua Marbun (Jurnal Ilmiah Satyagraha, 2024)
The tourism industry is an important sector in national development. Bali is aprovince in Indonesia which is well known for having extraordinary tourismpotential. Hotel is an accommodation facility that provides lodging facilities aswell as food and beverage services which are commercial in nature and aregrowing rapidly. The beauty of the beaches in Bali can be an added value for thehotel itself and an attraction for tourists who will stay at that place. The purposeof this study is to analyze the effect of Product Differentiation, Digital Marketingand Pricing Policies on Tourist Decisions di The Compass Rose Ubud.The research location is The Compass Rose Ubud Bali. The method ofdetermining the sample using the method purposive sampling. The sample of thisresearch is consumers or customers who are aged 17 years and over as many as110 respondents. The analysis technique used is multiple linear regressionanalysis.The results of the study show that product differentiation has a positive andsignificant effect on tourists' decisions at The Compass Rose Ubud. Digitalmarketing positive and significant effect on tourists' decisions The Compass RoseUbud. Pricing policy has a positive and significant effect on tourist decisions.Product differentiation, digital marketing and price policy has a positive andsignificant effect on tourists' decisions The Compass Rose Ubud. Differentiationvariables the product has the most dominant influence on tourists' decisions atThe Compass Rose Ubud.